2000
DOI: 10.1038/35004008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid movement of axonal neurofilaments interrupted by prolonged pauses

Abstract: Axonal cytoskeletal and cytosolic proteins are synthesized in the neuronal cell body and transported along axons by slow axonal transport, but attempts to observe this movement directly in living cells have yielded conflicting results. Here we report the direct observation of the axonal transport of neurofilament protein tagged with green fluorescent protein in cultured nerve cells. Live-cell imaging of naturally occurring gaps in the axonal neurofilament array reveals rapid, intermittent and highly asynchrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
368
6
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(427 citation statements)
references
References 34 publications
48
368
6
3
Order By: Relevance
“…With respect to motility, it has been demonstrated that peripherin and NF containing short filaments (or squiggles) move along MT tracks at rates up to 1-2 m/s in association with the molecular motors, kinesin, and cytoplasmic dynein (Yabe et al, 1999(Yabe et al, , 2000Prahlad et al, 2000;Shah et al, 2000;Wang et al, 2000;Helfand et al, 2002Helfand et al, , 2003. From these observations, it seems that the mechanisms governing the intracellular transport of short NF and peripherin squiggles are not fundamentally different from each other.…”
Section: Discussionmentioning
confidence: 79%
“…With respect to motility, it has been demonstrated that peripherin and NF containing short filaments (or squiggles) move along MT tracks at rates up to 1-2 m/s in association with the molecular motors, kinesin, and cytoplasmic dynein (Yabe et al, 1999(Yabe et al, , 2000Prahlad et al, 2000;Shah et al, 2000;Wang et al, 2000;Helfand et al, 2002Helfand et al, , 2003. From these observations, it seems that the mechanisms governing the intracellular transport of short NF and peripherin squiggles are not fundamentally different from each other.…”
Section: Discussionmentioning
confidence: 79%
“…As transport function B, the Rice distribution was used (Eq. [6] and Fig. 3a), which has very few components close to zero even for the minimum average velocity and resembles a Gaussian distribution for higher average velocity.…”
Section: Transport Functionsmentioning
confidence: 86%
“…[5][6][7]) were fitted to the ON data SI c (x,t) by optimizing the model parameters in order to minimize the L 1 and L 2 norm. Generally, the L p norm is given by:…”
Section: Model Fittingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in which fluorescent tags are placed on tubulin have allowed delineation of the microtubular organisation of the axon suggest that neurofilaments may move intermittently at fast speeds (up to 2 mm/s) interspersed with a period of no motion. 41 The overall result is of apparent slow axonal transport. A curious feature of this system is the wide variation in transport speeds for different molecules.…”
Section: Anterograde Transportmentioning
confidence: 99%